2020
DOI: 10.37121/jectr.vol1.114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of energy revenue and electrical power losses in distribution line

Abstract: This study presents the analysis of energy revenue and electrical power losses in distribution network, aimed to determine the energy losses on power distribution system. The 11kV power transmission line at Ujokuen community feeding to Benson Idahosa University was investigated. The following data were obtained as follow: energy delivered, energy billing, total cash amount, billed collected and correspond percentage. From the research work various technical power losses associated with power distribution netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Several previous studies that are relevant have been reported on electrolyte solutions of fruits such as used lime, lemon, grape, orange, coconut and watermelon (Osahenvemwen et al, 2020). Studied about electrolyte Performance of Noni (Morinda Citrifolia L.) fruit extracts (Akbar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies that are relevant have been reported on electrolyte solutions of fruits such as used lime, lemon, grape, orange, coconut and watermelon (Osahenvemwen et al, 2020). Studied about electrolyte Performance of Noni (Morinda Citrifolia L.) fruit extracts (Akbar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%